Spatiotemporal Changes of Calcitonin Gene-Related Peptide Innervation in Spinal Fusion - Zhou, Xiao-Yi (Biomed Res Int, 2016)
Few studies have investigated the role calcitonin gene-related peptide (CGRP) plays in the process of spinal fusion. The aim of the present study is to observe the temporal and spatial changes of CGRP induced by experimental fusion surgery in rats and elucidate the role of CGRP in spinal fusion. Male Sprague-Dawley rats were used in the study and the specimens were collected on the 7th, 14th, 21st, and 28th day, respectively. Then, histological and immunohistochemical analysis were applied to evaluate the fusion mass and spatiotemporal changes of CGRP chronologically. The results demonstrated that density of CGRP reached peak on the 21st day after surgery and most of the CGRP expression located surrounding the interface of allograft and fibrous tissue where the cells differentiate into osteoblasts, indicating that CGRP might be involved in the process of bone formation and absorption.